2015
DOI: 10.1002/berj.3177
|View full text |Cite
|
Sign up to set email alerts
|

The Simple View of Reading as a framework for national literacy initiatives: a hierarchical model of pupil‐level and classroom‐level factors

Abstract: Multilevel results showed independent distinct classroom-level effects for both D and LC with up to 68% of the classroom-level shared variance explained by these two components. Overall, the model fit thus suggests that the SVR is a good model for framing the underlying structure of classroom-level literacy attainment in grade 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Joshi & Aaron, 2012, for a recent description of an eco-systemic model and data on some of these candidate factors in RC). Furthermore, using listening comprehension as an index of the listening comprehension construct, while routine in the literature, may be an impoverished way of measuring the rather broad concept of LC more generally (see Savage et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joshi & Aaron, 2012, for a recent description of an eco-systemic model and data on some of these candidate factors in RC). Furthermore, using listening comprehension as an index of the listening comprehension construct, while routine in the literature, may be an impoverished way of measuring the rather broad concept of LC more generally (see Savage et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of individual differences in reading have shown that there are plenty of reasons for assuming that broader speech and language measures (typically assessed using listening comprehension or oral vocabulary tasks) load separately from word reading ability in factor analysis concurrently (Kendeou et al, 2009;Protopapas, Simos, Sideridis, & Mouzaki, 2012). Listening comprehension also emerges as a reliable distinct predictor of individual differences in RC over the early primary years (Catts, Hogan, & Fey, 2003;Demont & Gombert, 1996;Erdos, Genesee, Savage, & Haigh, 2011;Oakhill, Cain, & Bryant, 2003;Savage, Burgos, Wood, & Piquette, 2015;Verhoeven & van Leeuwe, 2012; although see also Carlisle & Felbinger, 1991;Diakidoy, Stilianou, Karefillidou, & Papageorgiou, 2005).…”
Section: Models Of Comprehension In Monolingual Instructional Contextsmentioning
confidence: 99%
“…Gough and Tunmer's seminal paper from 1986 theorised that: Reading = Decoding × Comprehension (R = D × C), which subsequently has been shown in countless studies to be relevant to understanding children's reading development (e.g. see Savage et al, 2015). It is important to note that Gough and Tunmer did not regard this model as a model of teaching, it is a model of children's reading development, although in their paper Gough and Tunmer acknowledged that reading development and the teaching of reading are interconnected.…”
Section: Theories Underpinning the Three Orientations To The Teaching...mentioning
confidence: 99%
“…Therefore, even if a child's oral language comprehension is high, an inability to decode will preclude comprehension of the text. To be sure, there are more nuanced (and complex) models of reading (e.g., Savage, Burgos, Wood, & Piquette, 2015), and even Gough and Tunmer acknowledged sublevels within a simple view of reading, but it is useful to examine decoding and comprehension in CMMHL because of the effect of auditory attenuation on these skills, and it is perhaps noteworthy that there is continued support in the literature for studying this dichotomy in typical development as well (Savage et al, 2015).…”
Section: Phonological Awareness Language and Readingmentioning
confidence: 99%